2003
DOI: 10.1046/j.1365-294x.2003.01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Social pairing and female mating fidelity predicted by restriction fragment length polymorphism similarity at the major histocompatibility complex in a songbird

Abstract: Female birds often copulate outside the pair-bond to produce broods of mixed paternity, but despite much recent attention the adaptive significance of this behaviour remains elusive. Although several studies support the idea that extra-pair copulations (EPCs) allow females to obtain 'good genes' for their offspring, many others have found no relationship between female mating fidelity and traits likely to reflect male quality. A corollary to the good genes hypothesis proposes that females do use EPCs to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 52 publications
5
121
0
1
Order By: Relevance
“…Several other studies not detailed here have also demonstrated MHC-dissimilar mating behaviour, including in Savannah sparrows Passerculus sandwichensis (Freeman-Gallant et al, 2003) and female sand lizards Lacerta agilis (Olsson et al, 2003(Olsson et al, , 2004.…”
Section: Mhc-dependent Sexual Selection Mate Choice and The Mhcsupporting
confidence: 57%
“…Several other studies not detailed here have also demonstrated MHC-dissimilar mating behaviour, including in Savannah sparrows Passerculus sandwichensis (Freeman-Gallant et al, 2003) and female sand lizards Lacerta agilis (Olsson et al, 2003(Olsson et al, , 2004.…”
Section: Mhc-dependent Sexual Selection Mate Choice and The Mhcsupporting
confidence: 57%
“…As noted in the introduction, information on HLA is available through body odor (16,17). It has been suggested that several vertebrate species use this information to select mates with dissimilar HLA (33)(34)(35)(36), and for this to occur, the olfactory system should have access to the information of self HLA makeup. In here finding that HLA is also linked to olfactory perception alone, our results combine with a previous effort (19) to provide a path for such self-recognition, and in this close a loop likely subserving behavioral selection mechanisms that rely on the sense of smell (20).…”
Section: Discussionmentioning
confidence: 99%
“…An exception to this was a study of pheasants, Phasianus colchicus, in which it was found that females preferred males with larger spurs, and that spur length was associated with MHC genotype (von Schantz et al 1997). In passerines, very recent work suggests a role for the MHC in both within-and extra-pair mate choice in the savannah sparrow, Passerculus sandwichensis (Freeman-Gallant et al 2003). In this species, young females (but not older birds) appeared to prefer MHC-dissimilar social mates, and high MHC similarity between social mates (all ages) was linked to the occurrence of EPP.…”
Section: Discussion (A) Mhc-based Mate Choicementioning
confidence: 99%
“…Extra-pair paternity (EPP) occurs in the majority of passerine bird species (Birkhead & Møller 1992;Griffith et al 2002) and may be a strategy used by females that are restricted in their choice of social mate to improve the genetic quality of their offspring (reviewed in Jennions & Petrie 2000;Tregenza & Wedell 2000). MHC-based extrapair mating may be important in passerines, but very few studies have addressed this question so far (Freeman-Gallant et al 2003;Westerdahl 2004).…”
Section: Introductionmentioning
confidence: 99%